Cowpea genetics: a review of the recent literature - Fery, R.; Singh, B. (1997)
In the decade since the literature on the genetics of cowpea was last reviewed by Fery (1985). Researchers have published numerous cowpea genetics studies, especially on economically important traits. Both qualitative and quantitative procedures have been utilized to study these traits, and considerable effort made to increase our knowledge of cowpea cytogenetics, heterosis, and problems associated with crossing cowpea with other Vigiia species. Many inheritance studies have addressed flower traits and earliness parameters, durations of specific developmental stages, pigmentation, nitrogen fixation, mycorrhizal colonization, seedling vigor traits, plant habit and root traits, leaf traits, pod trails, seed traits and grain quality, yield and yield components, fodder quality, heat and drought tolerances, resistance to bacterial, fungal and viral diseases, resistance to root-knot nematodes, resistance to insects, and resistance to parasitic weeds such as Striga gesnerioides and Aleclra vogelii.